2012
DOI: 10.1136/sextrans-2012-050619
|View full text |Cite
|
Sign up to set email alerts
|

Reaching black men who have sex with men: a comparison between respondent-driven sampling and time-location sampling

Abstract: Objectives We explored whether respondent-driven sampling (RDS) can generate a more diverse sample of Black men who have sex with men (MSM) than time-location sampling (TLS) by comparing sample characteristics accrued by each method in two independent studies. Methods The first study exclusively recruited Black MSM through RDS (N=256) while the second recruited MSM through TLS including a subsample of Black MSM (N=69). Crude and adjusted point estimates and 95% confidence intervals were calculated for socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 17 publications
2
42
2
Order By: Relevance
“…The Brazilian Ministry of Health adopted RDS for biological and behavioral surveillance for MSM. Comparing RDS to Time Location Sampling (TLS), another sampling method that may be used for hard-to-reach populations, RDS identified many more MSM in Fortaleza of low socioeconomic status 1,14 , a population with more public health relevance, and an outcome observed in other studies 14 . For these and other reasons, the Brazilian government 15 and Centers for Disease Control and Prevention (CDC) 16 , in the United States, recommend RDS as the method of choice for biological and behavioral and surveillance among key populations.…”
Section: Methodsmentioning
confidence: 99%
“…The Brazilian Ministry of Health adopted RDS for biological and behavioral surveillance for MSM. Comparing RDS to Time Location Sampling (TLS), another sampling method that may be used for hard-to-reach populations, RDS identified many more MSM in Fortaleza of low socioeconomic status 1,14 , a population with more public health relevance, and an outcome observed in other studies 14 . For these and other reasons, the Brazilian government 15 and Centers for Disease Control and Prevention (CDC) 16 , in the United States, recommend RDS as the method of choice for biological and behavioral and surveillance among key populations.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of age, the homophily indices were positive and relatively low for both 16-18-year-olds and 19-20-years-olds (i.e., homophily indices of 0.26 and 0.16, respectively); estimated network size was slightly larger for younger participants (mean=6.1 for those ages 16-18 versus 5.3 for those ages [19][20]. Population estimates mirror these statistics with adjustment down in the younger group and up in the older group to account for differences in homophily and network size (i.e., 42.4 % ages 16-18 in the sample versus 37 % in the population, 57.6 % ages 19-20 in the sample versus 63 % in the population, respectively).…”
Section: Evaluation Of Respondent-driven Sampling In a Study Of Youngmentioning
confidence: 99%
“…Others have suggested that different research participation payment structures are needed to incentivize YMSM in particular, 18 given low rates of participation. An alternative system was developed for adult MSM (e.g., raffle with large cash prize) in an RDSbased study; 31 however, any increase in incentive payments would need to be balanced with concerns about undue influence and/or coercion, 1 particularly for 20 these violate the RDS assumption of random recruitment. The proportion of seeds to sprouts found herein is remarkably similar to a parallel study of sexual minority youth conducted in Chicago at the same time as this study, 32 which provides additional evidence regarding the difficulty of RDS sampling in similar populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations